The Negative Mean Output Gap - Aiyar, Shekhar; Voigts, Simon (Washington, D.C. : International Monetary Fund, 2019)
We argue that in an economy with downward nominal wage rigidity, the output gap is negative on average. Because it is more difficult to cut wages than to increase them, firms reduce employment more during downturns than they increase employment during expansions. This is demonstrated in a simple New Keynesian model with asymmetric wage adjustment costs. Using the model's output gap as a benchmark, we further show that common output gap estimation methods exhibit a systematic bias because they assume a zero mean. The bias is especially large in deep recessions when potential output tends to be most severely underestimated.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet